2019
DOI: 10.1111/jam.14344
|View full text |Cite
|
Sign up to set email alerts
|

Stages of pregnancy and weaning influence the gut microbiota diversity and function in sows

Abstract: AimsThe gut microbiota is believed to play important roles in the health of pregnant mammals, including their nutrient metabolism, immune programming and metabolic regulation. However, until recently, the shifts in gut microbiota composition and faecal and blood metabolic activity during different stages of pregnancy had not been investigated.Methods and ResultsWe investigated the shifts in backfat thickness, plasma and faecal metabolites and gut microbiota on days 30, 60, 90 and 110 of pregnancy and on day 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
49
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 64 publications
9
49
1
Order By: Relevance
“…Generally, Firmicutes and Bacteroidetes were the most dominant phyla in most mammals [49]. In this study, Firmicutes and Bacteroidetes were indeed the most abundant phyla in all treatments regardless of the period, which was consistent with fecal microbiota from sows reported in previous studies [50,51]. However, sows fed SBP showed an increased abundance in phyla Tenericutes during gestation when compared with those fed WB.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, Firmicutes and Bacteroidetes were the most dominant phyla in most mammals [49]. In this study, Firmicutes and Bacteroidetes were indeed the most abundant phyla in all treatments regardless of the period, which was consistent with fecal microbiota from sows reported in previous studies [50,51]. However, sows fed SBP showed an increased abundance in phyla Tenericutes during gestation when compared with those fed WB.…”
Section: Discussionsupporting
confidence: 91%
“…HDL-C can transport TC to the liver for metabolizing to be other substances, thereby maintaining a stable TC level in the body [ 23 ]. The plasma TC and HDL-C levels were higher on day 21 of lactation than other stages in the present study, consistent with a previous report [ 6 ], suggesting that lipoprotein metabolism was enhanced in sows to offset the nutrient loss induced by lactation. Previous studies demonstrated that there is a diabetogenic status in late pregnancy, including high TG level, insulin resistance, and/or hyperglycemia, which could provide adequate nutrients to the fetuses, as well as fulfill the energy demands of infants during lactation [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating evidences demonstrate that gut microbiota governs host metabolism, and its composition varies in hosts in different physiological states [ 4 , 5 ]. Indeed, it has been well established that the gut microbiota composition is inconsistent in mammals during pregnancy [ 4 , 6 ]. For example, the gut microbiota changes dramatically from the first to the third trimesters of pregnancy (e.g., the increased Actinobacteria and Proteobacteria relative abundances and beta diversity and reduced individual richness) [ 4 ]; the intestinal microbiota composition is also dynamic in lactating mammals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that Christensenellaceae, Lachnospiraceae, and Escherichia coli are enriched during lactation in sows (Liu et al, 2019). Besides, another analysis of gut microbiome of the sow from pregnancy to weaning showed that the abundance of Tenericutes during lactation is significantly increased while Bacteroidetes and Fibrobacteres are decreased (Ji et al, 2019). These studies indicate that the gut microbiome during lactation is also in a state of disorder and continues the characteristics of pregnancy.…”
Section: Alterations Of Gut Microbiome During Lactationmentioning
confidence: 97%
“…During pregnancy, the changes of gut microbiome mainly include the decrease of individual richness (α diversity), the change of specific species richness and the increase of between-subject diversity (β diversity) (Koren et al, 2012;Chen et al, 2017). Table 3 summarizes alterations of gut microbiome during pregnancy (Koren et al, 2012;Gohir et al, 2015;Smid et al, 2018;Chen Y. et al, 2019;Ji et al, 2019;Liu et al, 2019).…”
Section: Alterations Of Gut Microbiome During Pregnancymentioning
confidence: 99%